2004
DOI: 10.1002/jssc.200301696
|View full text |Cite
|
Sign up to set email alerts
|

A liquid chromatography‐mass spectrometric method for the determination of oak moss allergens atranol and chloroatranol in perfumes

Abstract: This paper describes a validated liquid chromatographic-tandem mass spectrometric method for quantitative analysis of the potential oak moss allergens atranol and chloroatranol in perfumes and similar products. The method employs LC-MS-MS with electrospray ionization (ESI) in negative mode. The compounds are analysed by selective reaction monitoring (SRM) of 2 or 3 ions for each compound in order to obtain high selectivity and sensitivity. The method has been validated for the following parameters: linearity; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 12 publications
0
25
0
Order By: Relevance
“…The analysis can be performed by liquid chromatography‐mass spectrometry with a limit of detection of 2.4 p.p.b. (15). An initial screening analysis has shown that chloroatranol was present in perfumes up to a concentration of 8.3 p.p.m., which is close to the recommended maximum exposure of 9 p.p.m.…”
Section: Discussionmentioning
confidence: 99%
“…The analysis can be performed by liquid chromatography‐mass spectrometry with a limit of detection of 2.4 p.p.b. (15). An initial screening analysis has shown that chloroatranol was present in perfumes up to a concentration of 8.3 p.p.m., which is close to the recommended maximum exposure of 9 p.p.m.…”
Section: Discussionmentioning
confidence: 99%
“…Obviously, HPLC-MS/MS is the method of choice for the quantitative determination of these compounds, whether it be for measuring large concentrations in industrial extracts [37] or for trace determinations in cosmetic products. [38] Direct analysis of the volatile fraction of an oakmoss extract (an absolute) by GC, for example, is not straightforward if one bothers about the non-volatile fraction, which remains stuck in the chromatographic system, and, consequently, the necessity to use standardization.…”
Section: Quantitative Composition Of Oakmoss Extractsmentioning
confidence: 99%
“…Moreover, patch-testing on sensitized humans was performed only with synthetic atranol and chloroatranol, the purity of which was not known accurately, [75] despite repeated statements in the literature of a purity >99%. [1,38] Secondly, the removal of atranols leading to 'hyposensitizing' oakmoss extracts may not be as strictly selective as one would expect, thus leading possibly to biased conclusions regarding the true contribution of these components. [82] Undoubtedly, given the complexity of this problem and the present tendency to consider elicitation rather than induction, further bias-free experiments on both analytical and toxicological standpoints are desirable to establish the contributions of sensitizers in oakmoss extracts, either depsides or mono-aromatic compounds or both.…”
Section: Toxicological Issuesmentioning
confidence: 99%
“…E. prunastri contains atranorin and chloroatranorin, depsides that lead to the formation of atranol and chloroatranol during preparation of oak moss absolute. With methyl-β-orcinol carboxylate, they are potent allergens identified in oak moss absolute [261][262][263].…”
Section: Lichensmentioning
confidence: 99%